Integrasi Perencanaan Spasial Desa sebagai Safeguard dalam Upaya Mitigasi dan Adaptasi Perubahan Iklim Lokal - Ria Anjani; Fiki Nicola Rangga; Muhamad Muhdar (Fakultas Hukum Universitas Balikpapan, 2022)
This study aims to addressing the urgency of regulating spatial plans or village spatial planning as a safeguard in efforts to climate change mitigation and adaptation, as well as the legal position of village spatial planning in statutory regulations. Because Indonesia's involvement in various international conferences and has declared itself to be committed to reducing the effects of greenhouse gases also influences the direction of state policy. This commitment is contained and interpreted into various regulations that form the basis of development. In overcoming the rate of climate change, it must be in line with national to local scale policies. The relationship between the rate of climate change and mitigation and adaptation efforts starts from the structure of the smallest administrative area of the state, namely the village. Villages in the context of spatial planning are given the authority to regulate their land use according to local wisdom. In the regulatory aspect, village spatial planning requires regulations that can be used as guidelines and technical guidelines for village spatial planning by implementing sustainable and environmentally friendly development.